PENGARUH LATIHAN SKIPPING TERHADAP KEMAMPUAN SHOOTING SISWA SMPN 1 BUMI RAYA DALAM BERMAIN FUTSAL - M Ali Syahban; Ardhika Falaahudin (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to determine the effect of skipping training on the shooting ability of SMP N 1 Bumi Raya students in playing futsal. The research method used in this research is a quasi-experimental method using a one group pretest – posttest design. Quasi-experimental research is research with a quantitative approach in this research using the independent variable, namely skipping, and vice versa, the dependent variable is shooting ability. The population in the study was 10 students of SMP N 1 Bumi Raya. The sample uses a simple purposive sampling technique with the criteria of the skipping method as treatment. Time and place on the futsal field with 14 meetings. The research instrument used in this research is quantitative research which is measured by shooting ability and skipping training. The data analysis that I will use uses T-test analysis with (Paired T test) using SPSS 23. The conclusion is that there is an influence of skipping training on the shooting ability of SMP N 1 Bumi Raya students in playing futsal.